PENGARUH PEMBERIAN (ALBUMIN) IKAN KUTUK TERHADAP PENINGKATAN KADAR ALBUMIN PADA PASIEN POST OPERASI DENGAN HIPOALBUMIN DI RUANG GRAHA HITA RSUD dr. ISKAK TULUNGAGUNG - Indah Sri Wahyuni; Yuly Peristiowati; Sandu Siyoto (Universitas STRADA Indonesia, 2013)
Low albumin levels slow the immune response in the face of infection so that the healing process of wounds become too late and fish the curse is one of the producers of albumin source is high. The purpose of this research is to know the influence of allotment (albumin) fish curses to increased levels of albumin in patients post operation with hipoalbumin at the Graha Hita RSUD dr Iskak Tulungagung. Design his research pre his experiments with use the model one group pre-prosperous – test post test design. The population is all patients post an operation with hipoalbumin in space Graha Hita RSUD dr. Iskak Tulungagung. Sampling techniques used technique purposive sampling with large sample 20 respondents. Variable having an independent mind is giving ( albumin ) fish curse and variable dependen elevated levels of albumin. The instruments use pieces of observational. Time research conducted date 1 to 31 Desember 2012. Test statistics used paired t-test to level error (α) 0,05. The research results obtained by albumin levels before given (albumin) fish the curse of almost half of the respondents albumin levels less (< 3,5 g/dl) as 6 respondents (30%) and then given (albumin) fish almost almost all from the curse of the respondents albumin levels are normal (3.5-5 g/dl) as many as 17 respondents (85%). Analysis of the results obtained by the p-value value 0,000 < 0,05 which means influence awarding of 0.05 (albumin) fish curses to increased levels of albumin in patients post operation with hipoalbumin at the Graha Hita RSUD dr Iskak Tulungagung. The level of albumin after given ( albumin ) fish curse in patients post operation increase of respondents formerly levels of albuminnya less (< 3,5 g/dl) into normal (3.5-5 g/dl). With high ( albumin ) fish of the curse, then need to be given to the patient post surgery to help speed up the process of healing wounds former operation.